Psikologi Tokoh Utama Dalam Film Yuni - Aftita Alvi Pratiwi; Evi Chamalah (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The research aims to analyze the psychology of the main characters in Kamila Andini's Yuni film through the perspective of Sigmund Freud's psychoanalysis theory, focusing on the concepts of id, ego, and superego. Yuni's film depicts the struggles of a teenage girl in the face of patriarchal social and cultural pressures, including issues of sexual violence and early matchmaking traditions. The research method used is qualitative descriptive with viewing and recording techniques to collect data in the form of dialogue and scenes in films relevant to Yuni's id, ego, and superego representations. The research results show that the dynamics of all three aspects of Freud's personality played a significant role in shaping Yuni's response and actions to her various conflicts. Id Yuni manifested in basic urges and spontaneous desires, while ego served as a realistic mediator in dealing with social pressure and making decisions. Superego Yuni internalized the moral values and norms of society, which were often contrary to her personal desires. The study concluded that understanding of Yuni's identity, ego, and superego interactions provides a deeper insight into the psychological complexity of adolescents in strong socio-cultural contexts and issues of sexual violence. The research method used is qualitative descriptive. Data collection using the view and record techniques is accompanied by data validation. The data collected were then analyzed and grouped into Id, Ego, Superego. As for the results of this study, there are 7 data Id, 7 data Ego, and 7 data Superego. This study focuses on the psychology of the main characters and the solutions to prevent sexual violence. Thus it can be used as a reference and increase readers' knowledge and insight into Yuni's psychology in Freud's theories, namely Id, Ego, Superego.